Multipotent Capacity of Immortalized Human Bronchial Epithelial Cells - Delgado, Oliver (Public Library of Science, 2011)
While the adult murine lung utilizes multiple compartmentally restricted progenitor cells during homeostasis and repair, much less is known about the progenitor cells from the human lung. Translating the murine stem cell model to humans is hindered by anatomical differences between species. Here we show that human bronchial epithelial cells (HBECs) display characteristics of multipotent stem cells of the lung. These HBECs express markers indicative of several epithelial types of the adult lung when experimentally tested in cell culture. When cultured in three different three-dimensional (3D) systems, subtle changes in the microenvironment result in unique responses including the ability of HBECs to differentiate into multiple central and peripheral lung cell types. These new findings indicate that the adult human lung contains a multipotent progenitor cell whose differentiation potential is primarily dictated by the microenvironment. The HBEC system is not only important in understanding mechanisms for specific cell lineage differentiation, but also for examining changes that correlate with human lung diseases including lung cancer.